Chemical analysis of cascara tea from wine coffee processing with a different fermentation times. Issue 1 (February 2021) - Prono-Widayat, H; Arpi, N; Andini, R; Muzaifa, M; Gunawan, F
Abstract: Wine coffee is the result of processing coffee using a modified fermentation method. Currently, wine coffee is one of the most popular coffee products for coffee connoisseurs because of its strong and distinctive taste due to the fermentation process it goes through. Increased processing of wine coffee certainly increases the amount of waste produced. The aim of this research was to study the effect of fermentation time of wine coffee toward cascara tea quality. This study used a completely randomized design which consisted of 5 treatments and 3 replications. The treatment was fermentation times that consisted of F0 = control (no fermentation), F1 = 25 days of fermentation, F2 = 35 days of fermentation, F3 = 45 days of fermentation. The parameters analyzed were pH, total phenol and antioxidant activity. The results showed that the fermentation time of wine coffee affected the pH value of the cascara produced. Total phenol and antioxidant activity of cascara tea were not affected by fermentation time. It is necessary to analyze the level of consumer preference on the sensory quality of the resulting cascara tea.